Prevalence of Toxoplasmosis in Sheep Slaughtered in Ngampilan Slaughterhouse Yogyakarta Using CATT Method - Rika Yuniar Siregar; Yuswandi . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
The research was conducted to find out the prevalence of toxoplasmosis in sheeps which were slaughtered in Ngampilan Slaughterhouse Yogyakarta using card agglutination test (CATT) method. Blood samples were collected from 50 sheeps. The blood samples were then centrifuged at 5000 rpm for 5 minutes in 4°C in order to obtain the sera of the sheeps. After that, each serum in the amounts of 10 µl was tested using CATT method. The positive CATT test resulted in the green background with red aggregate in the middle, whereas the negative CATT test resulted in the uniform brown discoloration. In conclusion, about 72% of sheeps slaughtered in Ngampilan Slaughterhouse Yogyakarta was positively infected toxoplasma. Toxoplasmosis prevalences for ewes, rams, sheeps and lambs are 79 %, 59 %, 72 % and 67 %, respectively.